Sanctions economy: the strength of the “weak ties” of russian management - V. V. Stroev; O. A. Lomovtseva (Вестник университета)
The purpose of the article is to identify the risks of geo-economic fragmentation and deglobalization of integration during the period of the sanctions economy, their manifestation at the level of national economic entities, determination of overcoming factors. The subject of the study is the processes of adaptation of Russian business to the conditions of the global crisis of the pandemic period and anti-Russian sanctions, measures of state regulation of import substitution measures and reduction of supply chain gaps and partnerships. The main risks of globalization and integration of a socio-cultural nature are identified: distrust of government institutions, cross-cultural and ethno-humanitarian gaps, economic pessimism. One of the factors of containment of deglobalization gaps has been identified, which consists in the “weak ties” of existing partnerships, their relational capital. Examples of sustainable partnerships in business, science and education led to the conclusion that it is necessary to shift the emphasis in the training of managerial personnel to meritocratic principles of corporate theory, taking into account the interests of all stakeholders of companies and public sector organizations.